Work Psychology : Understanding Human Behaviour In The Workplace - Randall, Ray; Coyne, Iain; Patterson, Fiona; Arnold, John (Pearson International Content, 2020)
Gain a clear and authoritative introduction to human behaviour in the workplace Work Psychology, 7th edition, by Arnold, Coyne, Randall and Patterson is an accessible and fascinating examination of human behaviour in today’s workplace, written by authors who are all experts in their fields. Substantially updated with new chapters from new authors, and new material that reflects current research and debate in the area, the text retains its popular blend of theory, research and engaging examples. Covering a broad range of core topics, this text is suitable for undergraduate students in business, management, and psychology as well as those studying for professional qualifications. New to this edition: A clear and consistent structure, including an opening and closing case study and other exercises within each chapter to help you to apply what you’ve learnt Attractive full-colour design that aids navigation and enlivens the text Embedded within each chapter, coverage of diversity, technology and internationalization issues Learning outcomes, multiple-choice questions, discussion questions, a glossary, annotated further reading and weblinks to enable your learning within and beyond the textbook All the latest research and hot topics in the field of work psychology A ‘Key debate’ feature that directs you to key controversies and contemporary debate around work psychology today A ‘Research methods in focus’ feature that demystifies and illustrates with examples the use of strong research methods in practice A ‘Point of integration’ feature which clearly links the theories between chapters, allowing for a greater understanding of the topic as a whole Additional material for lecturers is available at go.pearson.com/uk/he/resources  John Arnold is Professor of Organisational Behaviour in the School of Business and Economics at Loughborough University. Iain Coyne is Senior Lecturer in Organisational Psychology, School of Business and Economics, Loughborough University, UK. Ray Randall is Senior University Teacher in Work Psychology, Institute of Work Psychology, Sheffield University Management School, UK. Fiona Patterson is Founder Director of the Work Psychology Group, Visiting Researcher, University of Cambridge and Visiting Professor, City University, London, UK.   Pearson, the world’s learning company.